Clinical profile of patients with fibromyalgia syndrome - Andrei Pereira Pernambuco; Lorena Rodrigues Terra da Silva; Angélica Cristina Souza Fonseca; Débora d'Ávila Reis
Abstract Introduction: The new diagnostic criteria for fibromyalgia (FM) include the presence of chronic, widespread pain associated with other symptoms such as fatigue, sleep disturbance, anxiety and depression. All these symptoms should be considered when thinking and clinical decision making of physiotherapists dealing with FM. However, it is clear that the other symptoms that accompany the pain are often neglected. Objective: To measure the levels of fatigue, sleep disturbances, anxiety and depression in patients with FM and compare them to levels found in healthy controls. Methods: Forty-six women diagnosed with FM and 30 healthy controls participated in the study. The levels of each of the symptoms were assessed by four validated questionnaires in Brazil (Piper Fatigue Scale - Revised, Pittsburgh Sleep Quality Index, Beck Anxiety Inventory and the Beck Depression Inventory). Statistical analysis was performed using GraphPad Prism software and all tests used a significance level of 5% (α = 0.05). Results: FM patients had significantly elevated levels of fatigue (p = 0.0005), sleep disturbances (p = 0.003), anxiety (p = 0.0012) and depression (p = 0.0003) compared to healthy controls. Symptoms fatigue and depression correlated strongly and positively with one another and with other symptoms evaluated. Conclusion: The other symptoms that comprise the clinical picture of FM need be considered not only in order to recover the health of patients, but above all in an attempt to preserve it and promote it.